Kyrgyz Republic : Staff Report for the 2002 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report, 2003)
This paper examines the Kyrgyz Republic's 2002 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility (PRGF), and a Request for Waiver of Performance Criterion. All performance criteria but one were observed for the period under review (April 1, 2002-September 30, 2002). The end-September targets on net international reserves and net domestic assets were met with wide margins. The fiscal deficit was within the program limit, despite the shortfall in revenues owing to the decline in real GDP. The target on tax collection was met thanks to improved tax administration.